Copper‐based Metal‐organic Framework for Non‐enzymatic Electrochemical Detection of Glucose. Issue 3 (10th January 2018) - Sun, Yanmei; Li, Yaxiang; Wang, Nan; Xu, Qing Qing; Xu, Ling; Lin, Meng
Abstract: A non‐enzymatic electrochemical glucose sensor based on a Cu‐based metal‐organic framework (Cu‐MOF) modified electrode was developed. The Cu‐MOF was prepared by a simple ionothermal synthesis, and the characterizations of the Cu‐MOF were studied by Fourier transform infrared spectroscopy (FT‐IR), scanning electron microscopy (SEM), thermogravimetric analysis (TGA), single‐crystal X‐ray powder diffraction (SCXRD), and X‐ray powder diffraction (XRD). Electrochemical behaviors of the Cu‐MOF modified electrode to glucose were measured by differential pulse voltammetry (DPV). The electrochemical results showed that the Cu‐MOF modified electrode exhibited an excellent electro‐catalytic oxidation towards glucose in the range of 0.06 μM to 5 mM with a sensitivity of 89 μA/mM cm 2 and a detection limit of 10.5 nM. Moreover, the fabricated sensor showed a high selectivity to the oxidation of glucose in coexistence with other interferences. The sensor was satisfactorily applied to the determination of glucose in urine samples. With the significant electrochemical performances, MOFs may provide a suitable platform in the construction of kinds of electrochemical sensors and/or biosensors and hold a great promise for sensing applications. Abstract :